Student's Challenges in Translating Poetry - Rahmawati Sukmaningrum; Arso Setyaji; Faiza Hawa (Borneo Educational Journal (Borju), 2023)
This article drawn from the local tracking study of how college students perceive the process of translating poetry. The aim of this study is to investigate the students’ challenge in translating poetry. The current study based upon the benefit of understanding poetry to build harmony in the society. Writers used descriptive qualitative research as the design of this study. The subject of the study were the sixth semester students of English Education Department of Universitas PGRI Semarang who had passed the Translation 1 subject and join the Translation 2 at the present time. The population of this study was 143 students in sixth semester. Writers then chose 20 students as the sample of this study. Students were assigned to translate English poem entitled ‘Huesca’ into Indonesian. The poem was written by John Conford, an American soldier who was endured on World War. After the assignment project, they were asked to respond the questionnaire related to the process of translating the poem and problems encountered. The finding revealed that most of students admitted that their biggest problem in poetry translation is associated with the linguistic difference. It refers to grammatical differences (source language and target language), lexical choices and meaning ambiguity. There were many factors behind the problems that encounter students in translating the English poem into Indonesian. Factors related to the culture, the use of figurative language, and the different structure between original poem and the target language are considered as main hindrances in translating literary works. The educational implication of the study is that our students need to be familiarized with literary works and its process of translation. However, since this study was only held in 2 months and had limited participants, the result of the study cannot be generalized. Further research, therefore, need to conduct by other researcher in order to get broader insight toward the theme